2019
DOI: 10.1002/lno.11155
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic signature of light and thermal stress for the endosymbiotic dinoflagellates of corals (Family Symbiodiniaceae)

Abstract: Coral reefs around the world have been affected by a climate‐change induced phenomenon known as “coral bleaching,” which is caused by the interaction between high irradiance and elevated seawater temperatures, and involves the mass expulsion of Symbiodiniaceae from anemones, sponges, and corals. The primary drivers of this phenomenon are the inherent genetic variability in the Family Symbiodiniaceae, and the variability in the abiotic environment for variables such as irradiance and temperature. Recent experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 86 publications
(166 reference statements)
0
24
0
Order By: Relevance
“…Indeed, we observed a significantly higher abundance of variants associated with Symbiodinium (clade A), Cladocopium (clade C), and Durusdinium (clade D) taxa in anemones that were preexposed to 32°C, but also in heat stressed individuals (that is, Aiptasia reared at 25°C and subsequently subjected to 32°C). Symbiodinium species are known to be more resilient, with lower reactive oxygen species levels and slower deterioration of photosystem (PS) II compared to Breviolum, for example [41,[59][60][61][62]. Surprisingly, despite S. linucheae (A4) being supposedly the most thermally tolerant species tested here (according to [32]), it was barely observed at 32°C; only in few individuals from 25°C and for which it was already present in their initial ITS2 composition.…”
Section: Discussionmentioning
confidence: 73%
“…Indeed, we observed a significantly higher abundance of variants associated with Symbiodinium (clade A), Cladocopium (clade C), and Durusdinium (clade D) taxa in anemones that were preexposed to 32°C, but also in heat stressed individuals (that is, Aiptasia reared at 25°C and subsequently subjected to 32°C). Symbiodinium species are known to be more resilient, with lower reactive oxygen species levels and slower deterioration of photosystem (PS) II compared to Breviolum, for example [41,[59][60][61][62]. Surprisingly, despite S. linucheae (A4) being supposedly the most thermally tolerant species tested here (according to [32]), it was barely observed at 32°C; only in few individuals from 25°C and for which it was already present in their initial ITS2 composition.…”
Section: Discussionmentioning
confidence: 73%
“…Studies that have examined the resistance of corals to predicted changes in OW and OA have resulted in variable results reflecting the interand intraspecific phenotypic plasticity of corals and their Symbiodiniaceae symbionts (Hoadley et al, 2015;Bahr et al, 2016; Castillo et al, 2018;Cole et al, 2018;Davies et al, 2018). For Symbiodiniaceae, the diversity in phenotypic characters related to the stress response is significant (Díaz-Almeyda et al, 2018;Lesser, 2019), and recent studies, including those on M. cavernosa, have shown that "symbiont shuffling" to stresstolerant Symbiodiniaceae (i.e., Durusdinium trenchi [Phylotype D1a]) can occur after exposure to thermal stress (Silverstein et al, 2015(Silverstein et al, , 2017Cunning et al, 2018). The change to, or addition of, D. trenchi symbionts to the Symbiodiniaceae community potentially adds resistance to future thermal perturbation (Silverstein et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The change to, or addition of, D. trenchi symbionts to the Symbiodiniaceae community potentially adds resistance to future thermal perturbation (Silverstein et al, 2015). While some studies incorporating both long and short-exposures of corals to combined OW and OA conditions have revealed little effect of OA on gene expression or the functional diversity of their Symbiodiniaceae (Baghdasarian et al, 2017;Davies et al, 2018), other studies on the functional responses of corals in response to OW and OA have shown significant effects where OA lowers the thermal response threshold of the coral (e.g., Anthony et al, 2008) when using ecologically relevant irradiances (sensu Lesser, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations